2005
DOI: 10.1111/j.1440-1797.2005.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy of potential cadaveric renal allografts at the time of retrieval

Abstract: A biopsy protocol for marginal potential renal allografts leads to acceptable allograft outcomes without significantly increasing allograft discardment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…They concluded that the kidneys from donors with ≥20% GS provide excellent outcome, being similar to the kidneys from donors with no GS. Verran et al [35] reported that 28/40 (70%) donors with renal allograft biopsies had <20% GS. One-year renal allograft survival was not significantly different between the protocol biopsied allografts versus the other non-biopsied allografts.…”
Section: Value Of Implantation Biopsymentioning
confidence: 99%
“…They concluded that the kidneys from donors with ≥20% GS provide excellent outcome, being similar to the kidneys from donors with no GS. Verran et al [35] reported that 28/40 (70%) donors with renal allograft biopsies had <20% GS. One-year renal allograft survival was not significantly different between the protocol biopsied allografts versus the other non-biopsied allografts.…”
Section: Value Of Implantation Biopsymentioning
confidence: 99%
“…Since Gaber et al showed the association between presence of more than 20% of sclerotic glomeruli in procurement biopsies and worsening in progression of the graft, this is still the main histological change in donors that is considered at the moment of the decision to accept or reject an organ . However, several studies have not found GS in biopsy specimens of donors to be a consistent marker of poor prognosis . Due to the use of wedge biopsy in our study, the IT analyses might be underestimated.…”
Section: Discussionmentioning
confidence: 67%
“…In United States, up to 85% of procured ECD kidneys are biopsied (2,17). High grade of glomerulosclerosis is a good predictor of early graft dysfunction (3), so this finding usually leads to organ discharge (18). Despite glomerulo-sclerosis is an important feature to allocation decision (1), its grade in effectively transplanted kidneys does not seem to be predictive of DGF or long-term kidney function in our series.…”
Section: Discussionmentioning
confidence: 69%
“…Many authors assume that none of the histological variables and scores provide perfect predictions and so results should be interpreted in the context of all available information on donor-recipients (2,18). A histological score is not the first test used during organ procurement to accept a kidney, but it is used successively to discard one.…”
Section: Discussionmentioning
confidence: 99%